The analysis of social competency and anti-social behaviors of children aged between 4 and 5 from the perspective of marital satisfaction and some other variables - CANEL, AZİZE NİLGÜN (ELSEVIER SCIENCE BV, 2012)
The data of this study was obtained from 174 pre-school children and their mothers. When the results of the study was investigated, a significant difference in the age variable was found for the children aged between 4-5 as a result of the independent t-test application of children's scores in 'self management and antisocial aggresive. The ANOVA test used to reveal whether the Social School Behavior Scales (SSBS) arithmetic means vary significantly depending on the families' educational level showed that the difference in the arithmetic means of their educational level is statistically significant in all the sub-scales, except for the sub-scale interpersonal skills (p<.05) According to another result of the study, the differences in the arithmetic means of marital satisfaction level in the subscales of SSBS's antisocial-aggresive and demanding-disruptive were found to be statistically difference (p<.05) as a result of the ANOVA test applied to determine whether the SSBS arithmetic means vary significantly depending on the families' marital satisfaction level.
Keywords: social skills; social competence; anti-social behaviors; marital satisfaction; pre-school education; PARENTAL DEPRESSION; PEER RELATIONSHIPS; CONFLICT; PERCEPTIONS; ADJUSTMENT; HOSTILITY; SKILLS